Pearls for Piggyback IOL Implantation - Suresh K Pandey; Vidushi Sharma (Delhi Journal of Ophthalmology)
Today’s cataract patients expect refractive results near emmetropia and relative independence from spectacles. The surgeon therefore needs to be skilled at multiple surgical methods for correcting residual ametropia after the cataract procedure. One useful method is to implant a piggyback IOL in the ciliary sulcus over the existing lens implant. In this issue we discuss the indications, contraindications, surgical technique, and complications involved with piggyback IOL implantation procedure. Piggyback technique of IOL Implantation was first described by Gayton and Sanders in 1993, this technique was initially developed to correct high hyperopic errors and as a secondary procedure to correct postoperative refractive errors. Implanting a second IOL in the posterior chamber is a relatively easy and atraumatic procedure that is not associated with the risk of potential complications seen with IOL exchange. Additionally, the accuracy of IOL power calculation is theoretically higher than in IOL exchange. Piggybacking with PMMA, silicone, or acrylic IOLs has been successful in myopic, hyperopic, and overcorrected pseudophakic patients. With the original IOL placed in the capsular bag, the piggyback IOL is traditionally placed in the sulcus in a brief procedure that takes just few minutes. Calculating the piggyback IOL power can be done quite accurately with the Holladay vergence formula. It is also easily estimated based upon the patient’s refraction. For myopic refractions, multiply the spherical equivalent by 1.2 to determine the piggyback IOL power. For hyperopic refractions, multiply the spherical equivalent by 1.5 to determine the piggyback IOL power. It is important to use an appropriate IOL for piggyback placement; these are three-piece IOLs that are made of hydrophobic acrylic, silicone or collamer material. Note that single-piece hydrophobic acrylic IOLs should not be placed into the sulcus because they may induce uveitis-glaucoma-hyphema syndrome.